Challenges in the treatment of late-identified untreated congenital adrenal hyperplasia due to CYP11B1 deficiency: Lessons from a developing country - Utari, Agustini; Faradz, Sultana M. H.; Ediati, Annastasia; Rinne, Tuula; Ariani, Mahayu Dewi; Juniarto, Achmad Zulfa; Drop, Stenvert L. S.; van Herwaarden, Antonius E.; Claahsen-van der Grinten, Hedi L. (Frontiers in Endocrinology, 2022)
Abstract Background: Congenital Adrenal Hyperplasia (CAH) due to CYP11B1 is a rare autosomal recessive adrenal disorder that causes a decrease in cortisol production and accumulation of adrenal androgens and steroid precursors with mineralocorticoid activity. Clinical manifestations include cortisol deficiency, ambiguous genitalia in females (differences of sex development (DSD)), and hypertension. Medical treatment recommendations are well defined, consisting of glucocorticoid treatment to substitute glucocorticoid deficiency and consequently normalize adrenal androgen and precursors levels. Current guidelines also emphasize the need for specialized multidisciplinary DSD teams and psychosocial support. In many developing countries, care for DSD patients, especially when caused by an adrenal disease, is challenging due to the lack of infrastructure, knowledge, and medication. Objective: The study aims to report the conflicting decision-making process of medical treatment and sex assignment in late-identified CAH patients in developing countries. Methods: We describe the clinical and biochemical findings and the psychological assessment of five affected but untreated family members with CAH due to CYP11B1 deficiency. Results: All patients had a 46 XX karyotype, ambiguous genitalia, low cortisol levels, and hypertension. Two identified as males, two as females, and one had undecided gender. The patients were counselled that refusing treatment will lead to infertility and the potential risk of developing Addisonian crisis and severe hypertension. However, all 46 XX CAH males refused treatment with glucocorticoids due to the expected lowering of adrenal androgens as their main source of testosterone. None of the patients developed Addisonian crisis, probably due to some residual cortisol activity and glucocorticoid activity of elevated adrenal steroid precursors. Conclusion: Medical treatment and sex assignment in late-identified 46 XX CAH patients in Indonesia may often depend on local and cultural factors. The management of DSD conditions may have to be individualized and integrated into the psychological and social context of the affected family.